2019
DOI: 10.1038/s41392-019-0062-9
|View full text |Cite
|
Sign up to set email alerts
|

Local delivery of arsenic trioxide nanoparticles for hepatocellular carcinoma treatment

Abstract: Hepatocellular carcinoma (HCC) is a malignancy with a poor prognosis. Surgery combined with chemotherapy has been recommended as a curative regimen for HCC. Nevertheless, the anticancer mechanisms of chemicals in hepatocellular carcinoma remain unclear. Pyroptosis is a type of programmed necrosis, and its mechanism in hepatocellular carcinoma is poorly understood. The efficacy and mechanism of arsenic trioxide nanoparticles in the treatment of HCC were explored in this research. Arsenic trioxide alone and arse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 39 publications
2
75
0
Order By: Relevance
“…Expression was decreased in etoposide-resistant melanoma cells and was negatively associated with cell resistance to etoposide-induced cell death. However, knockout of GSDME protected mice from various organ toxicities and body weight loss induced by chemotherapy drugs [66][67][68]. In the current study, DHP1808 induced less pyroptotic cell death than that of the combined Hsp90 and PI3K inhibitors in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 45%
“…Expression was decreased in etoposide-resistant melanoma cells and was negatively associated with cell resistance to etoposide-induced cell death. However, knockout of GSDME protected mice from various organ toxicities and body weight loss induced by chemotherapy drugs [66][67][68]. In the current study, DHP1808 induced less pyroptotic cell death than that of the combined Hsp90 and PI3K inhibitors in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 45%
“…Thus, the pyroptotic death will be a new target in cancer therapy. As2O3-NPs HCC Caspase3/GSDME [81] Natural products Galangin Glioblastoma LC3B/caspase3/GSDME [55] Anthocyanin OSCC NLRP3/caspase1/GSDMD [82] Dioscin Osteosarcoma Caspase3/GSDME [83] Berberine HCC Caspase1 [84] Huaier NSCLC NLRP3/caspase1 [85] ESCC: esophageal squamous cell carcinoma. OSCC: oral squamous cell carcinoma.…”
Section: Inducing Cancer Cell Pyroptosis For Cancer Therapymentioning
confidence: 99%
“…Wang et al showed that metformin, a widely used anti-diabetic drug, is able to activate the GSDMD-mediated pyroptosis of ESCC by targeting the miR-497/Proline-, glutamic acidand leucine-rich protein-1 (PELP1) pathway to treat ESCC [80]. Many studies have aimed to determine how to maintain therapeutic Arsenic trioxide (As2O3) concentrations in target solid tumor tissues for long period of time via activation of pyroptosis with few side effects [81,86,87]. Local drug delivery systems can extend the retention time of drugs' administration at the dosing site, resulting in more continuous efficacy and reduced side effects of normal tissues and organs [88,89].…”
Section: Non-chemotherapy Drug-induced Pyroptosis Exerts Anticancer Ementioning
confidence: 99%
See 1 more Smart Citation
“…This method is most notably used in the fight against cancer, where nanoparticles are an effective tool in localized chemotherapy. By delivering the therapeutic preparation locally, it is retained longer in the affected organ, which reduces the undesirable effect on the rest of the body [40][41][42]. Hu et al confirmed the effectiveness of arsenic trioxide nanoparticles in the fight against malignant liver cancer.…”
Section: Drug Carriersmentioning
confidence: 99%